Integration of Science and Religion in Pre-Marital Education Curriculum in Singapore - Yunos, Mohamad Yazid bin (Program Studi Magister Pendidikan Agama Islam, 2024)
Pre-marital education in Singapore is a form of government service to help prepare newly married couples to adjust and deal with problems at the beginning of marriage. This program is carried out in a professional manner and is structured according to scientific standards. This study was conducted to see how the concept of pre-marital education is carried out in Singapore, the concept of pre-marital education curriculum for Muslims, and the form of integration of science and religion in the pre-marital education curriculum. The research method used in this study is a qualitative method which produces descriptive data. The main data sources are Muslim brides who participate in educational programs and officers who are involved in pre-marital education programs. The data collection techniques are through observation, interviews, and documentation. The results of the study show that Pre-marital Education in Singapore is packaged in the form of Household Preparation Courses (KPBT) or Marriage Preparation Programs/Courses (MPP/C). This program is carried out professionally by government partner organizations appointed to organize, support and provide everything needed by couples who take part in pre-marital education programs. The ministry that oversees the implementation and registration of marriages is the Ministry of Social and Family Development (MSF). In this case APKIM Resources is the only Muslim organization or institution recognized by the Ministry of Social and Family Development (MSF) to organize the Household Preparation Course. The KPBT curriculum is compiled and determined by the Singapore Islamic Religious Council (MUIS) with the aim, content, process, and evaluation directed at preparing brides-to-be to navigate the flow of change when they step into the household level. The process of implementing pre-marital education involves the integration of knowledge and faith to understand, digest, and implement it. Without these two things, the process will not run optimally. Abstrak Pendidikan Pra Nikah di Singapura merupakan bentuk pelayanan pemerintah untuk membantu mempersiapkan pasangan yang baru menikah untuk menyesuaikan diri dan menghadapi masalah di awal pernikahan. Program ini dilaksanakan secara profesional dan terstruktur sesuai standar keilmuan. Penelitian ini dilakukan untuk melihat bagaimana konsep pendidikan pranikah yang dilakukan di Singapura, konsep kurikulum pendidikan pranikah bagi umat Islam, dan bentuk integrasi ilmu dan agama yang ada dalam kurikulum Pendidikan Pra Nikah. Metode penelitian yang digunakan dalam penelitian ini adalah metode kualitatif yang menghasilkan data deskriptif. Sumber data utama adalah calon pengantin muslim yang mengikuti program pendidikan dan petugas yang terlibat dalam program Pendidikan Pra Nikah. Teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa Pendidikan Pra Nikah di Singapura dikemas dalam bentuk Kursus Persiapan Rumah Tangga (KPBT) atau Marriage Preparation Programs/Courses (MPP/C). Program ini dilaksanakan secara profesional oleh organisasi mitra pemerintah yang ditunjuk untuk mengorganisir, mendukung dan menyediakan segala sesuatu yang dibutuhkan oleh pasangan yang mengikuti program pendidikan pranikah. Kementerian yang membawahi penyelenggaraan dan pencatatan perkawinan adalah Kementerian Sosial dan Pembangunan Keluarga (MSF). Dalam hal ini APKIM Resources adalah satu-satunya organisasi atau lembaga Muslim yang diakui oleh Kementerian Sosial dan Pembangunan Keluarga (MSF) untuk menyelenggarakan Kursus Persiapan Rumah Tangga (KPBT). Kurikulum KPBT disusun dan ditetapkan oleh Majelis Ugama Islam Singapura (MUIS) dengan tujuan, isi, proses, dan evaluasi yang diarahkan untuk mempersiapkan calon pengantin menghadapi arus perubahan ketika mereka melangkah ke tingkat rumah tangga. Proses pelaksanaan pendidikan pranikah melibatkan integrasi ilmu dan iman untuk memahami, mencerna, dan melaksanakannya. Tanpa kedua hal tersebut, proses tidak akan berjalan secara maksimal.